The visual field of blackness : identity formation through the self and the other. - Yasyeera Abdul Rahim. (2011)
Imagine yourself in a black hole. With no prior knowledge of the existence of light, the darkness of the hole becomes all that you have known. In the darkness, you attain a level of peace and solitude. You find no wrong in being in the dark and in fact, your surrounding becomes part of who you are. There is a sense of belonging and comfort in the familiarity of the darkness. There is no room for desire because the presence of the Other, light, is omitted. The self is contented. Now, imagine a ray of white light illuminating the previously black hole. The light carries the limitless possibilities, which darkness was never able to offer. The self begins to recognize the presence of the Other. In the recognition, the self is enamored by the lure of the Other.